Exploring The Missing Link: Sociodemographic Factor, Investment Knowledge and Behavioural Bias In Investment Decision - Ahmad Syarif; Maulana Farizi; Irma Yuliani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Investment plays a vital role in the financial planning of individuals. Generally, the investments typically employed in Indonesia are those associated with the capital market. The Indonesian capital market plays a pivotal role in promoting the country's economy and allowing the allocation of funds for businesses. An actual market crash in the Indonesian capital market resulted in a significant decline in share values. The current circumstances require a conversation about the importance of understanding the role of individual investors as vital contributors to investment decision-making in the market. Empirical research has demonstrated that the behavioural bias of individual investors during times of disruption is a significant element contributing to market declines in the capital market. This study examines the impact of investment knowledge and sociodemographic factors on investment decision-making, specifically focussing on behavioural bias. This research method is a quantitative approach by utilising a questionnaire to collect data from 150 investors who are part of the sharia investment community. The variables examined in this study encompass investment knowledge, behavioural bias, sociodemographic factor, and investment decisions.The study demonstrates that investment knowledge and behavioural biases have a substantial impact on investment choices. Investment decisions are significantly influenced by sociodemographic characteristics. Investment decisions are significantly influenced by knowledge and sociodemographic characteristics. Behavioural bias has a role in influencing investment decisions in the disruptive period, by interacting with information and sociodemographic factors. In light of the ongoing era of rapid transformation and advancement, it is crucial for investors to promptly attain financial literacy, as knowledge pertaining to Islamic financial products is easily accessible. Stakeholders should establish an educational program focused on Islamic financial market literacy to improve knowledge and understanding of investing.